Pop-in phenomenon at nanoindentation and fracture toughness of two-phase ceramic composites. (2023) - Sadowski, Tomasz; Łosiewicz, Kamil
Abstract: Material's resistance to crack propagation corresponds to its fracture toughness. This characteristic can be calculated in laboratory tests, e.g. 3-point bending of notched bars or by indentation test. Spherical, conical, or pyramidal tips can be used during nanoindentation and micro indentation tests, e.g. Vickers, Berkovich, or Cube-Corner tip. The lower level of fracture toughness is a key parameter of ceramic materials and this attribute is not frequently investigated by nanoindentation. If the load force is quite small, an extra increase in penetration depth can occur, which can be described as the pop-in phenomenon. This paper shows the results of nanoindentation tests with the use of cube-corner tips and load levels of 2 mN and 5mN. Five types of ceramic composites Al2 O3 /ZrO2 with composition ratios of 20, 40, 60, and 80 wt% of Al2 O3 content were tested. To estimate the fracture toughness by calculating the crack length force–displacement curves with visible pop-in phenomenon were selected for analysis.